ITRAQ-based quantitative proteomics analysis of Sprague-Dawley rats liver reveals perfluorooctanoic acid-induced lipid metabolism and urea cycle dysfunction. (1st March 2022) - Liu, Hui; Sun, Weiqiang; Zhou, Yongbing; Griffin, Nathan; Faulkner, Sam; Wang, Li
Graphical abstract: Highlights: PFOA cause liver damage and influence urea synthesis. PFOA has effects on sera biochemical parameters, which are ALT, GGT, BILD and UREA. iTRAQ-based quantitative proteomics analysis revealed 112 significantly upregulated proteins and 80 downregulated proteins. 8 proteins were associated with fatty acid oxidation and 2 proteins were associated with urea cycle. Abstract: Perfluorooctanoic acid (PFOA) is a typical C8 representative compound of perfluoroalkyl and polyfluoroalkyl substances (PFAS) widely used in industrial and domestic products. It is a persistent organic pollutant found in the environment as well as in the tissues of humans and wildlife. Despite emerging scientific and public interest, the precise mechanisms of PFOA toxicity remain unclear. In this study, male rats were exposed to 1.25, 5, and 20 mg PFOA/kg body weight/day for 14 days by gavage; food intake and bodyweight changes were recorded every day. After 14 days, blood was collected for sera biochemistry, livers were quickly stripped and weighed after execution. Part of the liver tissue was frozen by liquid nitrogen for iTRAQ-Based Quantitative Proteomics Analysis; and some was fixed in 4% paraformaldehyde (PFA) for histological section and hematoxylin-eosin (HE) staining. Urine samples were also collected and monitored by raising rats in metabolic cages. Real-time quantitative PCR and western blot was used to validate the proteomics assay after bioinformatics analysis. The results demonstrate that 20 mg/kg/d PFOA exposure cause body weight loss and significant liver swelling and reduced urea metabolism. The sera biochemistry assay shows that ALT, GGT, BILD and UREA levels have significant changes compared with normal control group and reference range of rat sera. The subsequent iTRAQ-based quantitative proteomics analysis of rat livers identified 3, 327 non-redundant proteins of which 112 proteins were significantly upregulated and 80 proteins were downregulated. Gene ontology analysis revealed proteins are primarily involved in cellular, metabolic and single−organism processes. Among them, eight proteins (ACOX1, ACOX2, ACOX3, ACSL1, EHHADH, GOT2, MTOR and ACAA1) were related to oxidation of fatty acids and two proteins (ASS1 and CPS1) were found to be associated with urea cycle disorder. The downregulation of urea synthesis proteins ASS1 and CPS1 after exposure to PFOA was then confirmed through qPCR and western blot analysis. Together, these data demonstrate that PFOA exposure directly influences urea metabolism and provides insight into specific mechanisms of hepatotoxicity as a result of PFOA exposure.